The Influence of Service Quality and Price on Inpatient Treatment Decisions at Mitra Sejati General Hospital with Consumer Satisfaction as an Intervening Variable - Epinaldi Inganta Pratama Ginting; Galumbang Hutagalung; Nagian Toni (Publisher Cv. Inara, 2022)
The purpose of this study is to determine the influence of Service Quality and Price to Decision Inpatient Treatment in RSU Mitra Sejati with Consumer Satisfaction as an Intervening Variable. The sample in this study as many as 100 Respondents hospitalization. This research using SPSS Version 23. The results showed the Quality of Service has a Positive influence on the Decision of Inpatient Treatment in RSU Mitra Sejati. Price has a positive effect on the Decision of Inpatient Treatment in RSU Mitra Sejati Decision of the Treatment has a positive influence on Consumer Satisfaction in RSU Mitra Sejati. Service quality has a Positive influence on Consumer Satisfaction in RSU Mitra Sejati. Price has a positive influence on Consumer Satisfaction in RSU Mitra Sejati. Service quality has a positive influence on the Decision of the Inpatient Treatment through customer Satisfaction as an intervening variable. Price has a positive influence on the Decision Beorbat Hospitalization through customer Satisfaction as an intervening variable.